Educational Transformation with a Love-Based Curriculum: Teacher and Student Perspectives at MA Assa'adah Depok, West Java - Siti 'Aisyatunnadiya; Putri Julia; Iqbal Nuzula (Journal of Islamic Education and Intellectual Discourse (JIED), 2025)
This research aims to analyze educational transformation through the implementation of the Love-Based Curriculum (LBC) at MA Assa'adah, by examining the perspectives of teachers and students. LBC is seen as an educational approach that emphasizes a balance between cognitive, affective, and psychomotor aspects, and is founded on compassion, empathy, and caring. The research methodology uses a qualitative approach with a case study design, employing observation, interviews, and documentation. Data analysis was carried out through reduction, presentation, and verification, with triangulation used to test data validity. The findings indicate that LBC is understood as an effort to create a humanizing learning environment for students, with teachers acting not only as knowledge transmitters but also as educators who instill values of love and care. The learning methods used are no longer solely lecture-based but place more emphasis on active student participation through discussions, group work, and collaborative projects that foster a sense of belonging and togetherness. However, the implementation of LBC still faces constraints, such as a lack of teacher understanding, limited resources/media, student resistance, curriculum density, and minimal professional training. Thus, LBC can be an educational transformation strategy that focuses not only on academic achievement but also on the holistic development of character and human values. If implemented consistently and supported by appropriate policies, LBC has great potential to produce a generation that is not only intellectually intelligent but also possesses social sensitivity, empathy, and the ability to cooperate in a diverse society. This transformation is expected to address the challenges of the Society 5.0 educational era, which demands a balance between cognitive, emotional, and spiritual intelligence.